Particle Physics with ORCA - Domi Alba (EPJ Web of Conferences, 2019)
KM3NeT is a Megaton-scale neutrino telescope currently under construction at the bottom of the Mediterranean Sea. When completed, it will consist of two separate detectors: ARCA (Astroparticle Research with Cosmics in the Abyss), optimised for high-energy neutrino astronomy, and ORCA (Oscillation Research with Cosmics in the Abyss) for neutrino oscillation studies of atmospheric neutrinos. The main goal of ORCA is the determination of the neutrino mass ordering (NMO). Nevertheless it is possible to exploit ORCA’s configuration to make other important measurements, such as sterile neutrinos, non standard interactions, tau-neutrino appearance, neutrinos from Supernovae, Dark Matter and Earth Tomography studies. Part of these analyses are summarized here.